INNOVATIVE WAYS TO IMPROVE THE EFFICIENCY OF TRADE POLICY IN UZBEKISTAN - S.N.Yuldasheva (Galaxy International Interdisciplinary Research Journal, 2022)
This article provides analytical information about the country’s foreign economic activity, trade policy, the process of its implementation, factors affecting the country’s foreign policy, the volume of exports and imports of the country.